Diabetic kidney disease in rural Australia: prevention, management, treatment and way forward - Allen G. Ross; Utpal K. Mondal; Anayochukwu E. Anyasodor; Shakeel Mahmood; Feleke H. Astawesegn; M. Mamun Huda; Subash Thapa; Setognal B. Aychiluhm; Santosh Giri; Md. Ferdous Rahman; Muhammad J. A. Shiddiky; Mohammad A. Moni; et al. (Frontiers in Medicine)
Diabetic kidney disease is a significant microvascular complication associated with chronic diabetes, contributing substantially to the overall health burden of the disease. This perspective focusses on evaluating the most recent advancements in screening techniques, prevention, and treatment strategies along with new advances in the field. A comprehensive literature search was conducted across PubMed, Scopus and Google Scholar databases to identify and synthesize recent evidence. In Australia, chronic kidney disease (CKD) was responsible for approximately two million hospital admissions, accounting for 18% of all hospitalizations in 2021–22. In remote areas, 17,100 CKD-related hospitalizations were reported during this period, with residents being three times more likely to be hospitalized for CKD compared to those living in major cities. Among First Nations people, the burden was 7.8 times higher than that of non-Indigenous populations. Advocacy for policy changes to address healthcare disparities in rural and remote Australia is crucial.